A comprehensive review on anticorrosive behaviour of surfactants across diverse metals using multiple techniques: Current insights and future horizons - Pavitra Shenoy; Namitha Kedimar; Suma A. Rao (Chemical Engineering Journal Advances)
Corrosion is one of the crucial topics of concern, as it has caused a lot of economic losses in many countries across the world. Various measures have been taken over the years to tackle corrosion, amongst which corrosion inhibitors have taken the limelight. As far as we know, there hasn't been any published work that brings together all the research on how different types of surfactants can prevent corrosion on different materials. This review covers 100+ surfactants acting as corrosion inhibitors for different metals, providing a comprehensive and accessible resource. Surfactants possess unique properties such as their adequate hydrophilic to hydrophobic ratio, presence of halogen atoms, and diversity due to charge variations, making them a potential corrosion inhibitor. Surfactants containing long hydrophobic tails, electronegative atoms, and smaller spacer sizes showed increased inhibition efficacy. This paperarticle summarizes the type of metal and medium upon which the surfactant acted and hence protected metal corrosion. In addition, studies have explained about the type of surfactants, the electrochemical, spectroscopic, computational simulations, and different adsorption isotherms. The significance of the literature is to provide the readers with a library of surfactants possessing corrosion inhibition properties against various materials and to maintain sustainability.